Alternaria species in section Alternaria associated with Iris plants in China - Gou, Ya-Nan; Aung, Sein Lai Lai; Htun, Aye Aye; Huang, Cheng-Xin; Deng, Jian-Xin (Frontiers in Microbiology, 2022)
Plants of the Iris genus have been widely cultivated because of their medicinal, ornamental, and economic values. It commonly suffers from Alternaria leaf spot or blight disease leading to considerable losses for their commercial values. During an investigation of 14 provinces or municipalities of China from 2014 to 2022, a total of 122 Alternaria strains in section Alternaria were obtained from diseased leaves of Iris spp.. Among them, twelve representative strains were selected and identified based on morphological characterization and multi-locus phylogenetic analysis, which encompassed the internal transcribed spacer of rDNA region (ITS), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), translation elongation factor 1 alpha (TEF1), RNA polymerase second largest subunit (RPB2), Alternaria major allergen gene (Alt a 1), an anonymous gene region (OPA10-2), and endopolygalacturonase gene (EndoPG). The strains comprised two known species of A. alternata and A. iridicola, and two new species of A. setosae and A. tectorum, which were described and illustrated here. Their pathogenicity evaluated on Iris setosa indicated that all the strains could induce typical Alternaria leaf spot or blight symptoms. The results showed that the virulence was variable among those four species, from which A. tectorum sp. nov. was the most virulent one, followed by A. setosae sp. nov., A. iridicola and A. alternata.